2017
DOI: 10.1515/revneuro-2016-0044
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and vitamin D: a comprehensive review of current knowledge

Abstract: AbstractVitamin D has been considered as neurosteroid, and its pivotal role in neuroprotection, brain development, and immunomodulation has been noticed in studies; however, our knowledge regarding its role in neurological disorders is still developing. The potential role of vitamin D in the pathophysiology and treatment of epilepsy, as one the most prevalent neurological disorders, has received less attention in recent years. In this article, we review the possible relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 161 publications
1
13
0
1
Order By: Relevance
“…Various associations have been reported between vitamin D status and brain diseases, such as epilepsy. 25-OH-vitamin D3 supplementation results in improved seizure control in patients with pharmaco-resistant epilepsy (Holló et al, 2012; Miratashi et al, 2017). In 2013, Zhao et al reported a correlation between 25-OH-vitamin D3 deficiency and the prevalence of Alzheimer’s and Parkinson’s diseases (Oudshoorn et al, 2008; Zhao et al, 2013).…”
Section: Vitamin D3 In Neurological Disordersmentioning
confidence: 99%
“…Various associations have been reported between vitamin D status and brain diseases, such as epilepsy. 25-OH-vitamin D3 supplementation results in improved seizure control in patients with pharmaco-resistant epilepsy (Holló et al, 2012; Miratashi et al, 2017). In 2013, Zhao et al reported a correlation between 25-OH-vitamin D3 deficiency and the prevalence of Alzheimer’s and Parkinson’s diseases (Oudshoorn et al, 2008; Zhao et al, 2013).…”
Section: Vitamin D3 In Neurological Disordersmentioning
confidence: 99%
“…The study of anticonvulsant medication influence on Vitamin D rate is extremely important, this fact being confirmed by a large number of foreign publications devoted to this issue [1][2][3][4][5]. For instance, Sharma А. et al in their article "A complication of valproate therapy and a thought beyond Vitamin D deficiency" suggested that a long-term use of Vitamin D supplements for 6 months in combination with Carnitine and discontinuation of Sodium Valproate promoted the recovery of patients with proximal myopathy [6].…”
Section: Introductionmentioning
confidence: 96%
“…Recently, hypovitaminosis D was also reported in children with epilepsy receiving anti-seizure medications (ASMs), especially enzyme-inducing ASMs (EIASMs) ( 11 13 ). EIASMs exert their effects on destructing VitD status via inducing cytochrome P450 ( 14 ). However, it still remains controversial over the effects of valproic acid (VPA) – a type of non-enzyme-inducing ASMs (NEIASMs), on the VitD levels.…”
Section: Introductionmentioning
confidence: 99%